ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) PADA PARAMEDIS - Puji Astuti; Erita Yuliaseti Diah Sari; Herlina Siwi Widiana (Jurnal Psikologi Integratif, 2019)
Abstract. Organization needs high quality employees who are willing to work outside their main tasks to support organizational performance. This willingness is known as organizational citizenship behavior (OCB) that may influenced by supportive leadership style, perceptions of organizational culture and intrinsic job satisfaction. This study aimed to explore the effect of supportive leadership style, perceptions of organizational culture and intrinsic job satisfaction on OCB. Subjects involved in this study were 68 paramedics of a private hospital in Special Region of Yogyakarta. Data were collected using three scales, and then analyzed with multiple regression. Results show that supportive leadership style, perception of organizational culture and intrinsic job satisfaction significantly predict OCB among paramedics. Perception of organizational culture have the biggest contribution in predicting OCB, followed by intrinsic job satisfaction and supportive leadership style. Improving supportive leadership styles, perceptions of organizational culture and intrinsic job satisfaction will increase the OCB of the employees.Keywords: organizational citizenship behavior, paramedics  Abstrak. Sebuah organisasi perlu memiliki pegawai yang berkualitas dan bersedia bekerja di luar tugas utamanya untuk mendukung kinerja. Kesediaan ini disebut dengan organizational citizenship behavior (OCB) yang dapat dipengaruhi oleh gaya kepemimpinan suportif, persepsi budaya organisasi dan kepuasan kerja intrinsik. Penelitian ini bertujuan untuk mengeksplorasi pengaruh gaya kepemimpinan suportif, persepsi budaya organisasi dan kepuasan kerja intrinsik terhadap OCB. Sebanyak 68 orang tenaga paramedik sebuah rumah sakit berpartisipasi dalam penelitian ini. Pengumpulan data menggunakan skala organizational citizenship behavior, skala gaya kepemimpinan suportif, skala persepsi budaya organisasi dan skala kepuasan kerja intrinsik. Analisis regresi berganda digunakan dalam proses analisis data. Hasil penelitian  menunjukkan bahwa gaya kepemimpinan, persepsi budaya organisai dan kepuasan kerja intrinsik secara signifikan mampu memprediksi OCB. Persepsi terhadap budaya organisasi memiliki sumbangan efektif terbesar,  diikuti oleh kepuasan kerja intrinsik dan gaya kepemimpinan suportif. Dengan meningkatkan gaya kepemimpinan suportif, persepsi terhadap budaya organisasi dan kepuasan kerja intinsik maka akan diikuti peningkatan OCB.Kata Kunci:  organizational citizenship behavior, paramedis